Living Mysteries: Embodiment of Divine Knowledge in Jewish Apocalypticism - Orlov, Andrei A. (Gnosis, 2022)
The study explores the early Jewish understanding of divine knowledge as divine presence, which is embodied in major biblical exemplars, such as Adam, Enoch, Jacob, and Moses. It demonstrates that the personification of divine knowledge in early Judaism and, especially, in the Jewish pseudepigrapha reveals a distinct “cultic” way of mediating the divine presence and, consequentially, the divine knowledge that can be designated as the “divine presence’s epistemology.”